Education of Teachers - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 1993)
The article discusses the problems of teacher education, with a special emphasis placed on one of them – pedagogy course is too theoretical. Failing to apply the theory in practice calls into question the benefits of pedagogy itself, even leads to consideration whether pedagogy is a science rather than a mere list of needs, ideal suggestions, and ideological statements. Linking theory with practice would strengthen both the authority of pedagogy and its utility. It is necessary to pay more attention to the following pedagogical practice areas in teacher education: the activation of self-consciousness, relationships, communication, evaluation, counselling, care, leadership skills, and technologies of learning. First of all, educators rather than teachers should be trained. More attention should be paid to pedagogical practice. Of course, the role of the theory and history of pedagogy should not be devalued in teacher education. It is also important that the students have knowledge of educational philosophy and psychology, are aware of the educational systems of various countries.